Disposition and Absolute Bioavailability of Oral Imlunestrant in Healthy Women: A Phase 1, Open-Label Study - Datta-Mannan, Amita; Czeskis, Boris; Shanks, Elaine; Yuen, Eunice; Hall, Stephen; Rodriguez Cruz, Vivian; Cassidy, Kenneth (Clinical pharmacology in drug development, 2025)
Imlunestrant (LY3484356) is a next-generation orally bioavailable selective estrogen receptor degrader being investigated for the treatment of estrogen receptor-positive advanced breast and endometrial cancers. This Phase 1, open-label, 2-part study evaluated the disposition and absolute bioavailability of [ C]-imlunestrant in 16 US-based healthy women (aged 36-65 years) of non-childbearing potential. Part 1 participants (N = 8) received an oral dose of 400-mg [ C]-imlunestrant solution (100 µCi). Part 2 participants (N = 8) received an oral dose of 2 × 200-mg imlunestrant tablets followed by approximately 45 µg [ C]-imlunestrant (approximately 1 µCi) given as a 15-minutes infusion 4 hour later. Blood, fecal, and urine samples were collected. Total radioactivity was primarily eliminated in feces (97.3%) with trace amounts recovered in urine (0.278%), suggesting minimal renal clearance. Imlunestrant accounted for most of the radioactive dose in feces (61.8%), followed by metabolite M2 (20.9%), metabolites M5 + M10 (coeluted), M7, M8, M9, and M11 (5.1% or less for each). Absolute bioavailability of imlunestrant after oral administration relative to intravenous administration was 10.9% based on dose-normalized area under the concentration-time curve from time zero to infinite time. Imlunestrant was well tolerated as an oral solution or as a tablet/intravenous dose. Eight participants reported mild/moderate treatment-related adverse events that resolved by the end of the study.